Highly porous tungsten-oxide-based films obtained by spray-gel for gas sensing applications - Solís, José (2005)
Highly porous mixed WO3–SnO2 films have been prepared from an aqueous solution of SnCl4.5H2O and polytungsten gel with a molar ratio of Sn/W from 0 to 1. These solutions were sprayed on to alumina substrates at 220 ºC. The obtained films were annealing at 600 ºC in air for 3 h. The annealed films were composed of a mixture of WO3 and SnO2 phases. The gas sensitivity to butanol and ethanol vapors is enhanced when the Sn/W molar ratio increases in the film by up to 0.1, with further increments to this proportion the sensitivity decreases.